Persistence of de novo donor-specific HLA-antibodies after lung transplantation: a potential marker of decreased patient survival - Schmitzer, Magdalena; Winter, Hauke; Kneidinger, N.; Meimarakis, G.; Dick, A.; Schramm, R.; Klotz, Laura Valentina; Preissler, G.; Strobl, N.; Dossow, V. von; Schneider, C.; Weig, T.; et al. (HLA, 2018)
The impact of de novo donor-specific anti-HLA-antibodies (donor-specific antibody [DSA]) on outcomes in lung transplantation is still a matter of debate. We hypothesize that differentiating DSA by persistent and transient appearance may offer an additional risk assessment. The clinical relevance of HLA-antibodies was investigated prospectively in 72 recipients with a median follow-up period of 21 months. The presence of HLA-antibodies was analysed by a single antigen bead assay before and after (3 weeks, 3, 6, 12 and 18 months) transplantation. In 23 patients (32%), de novo DSAs were detected. In 10 of these patients (44%), DSA persisted throughout the follow-up period, whereas 13 of these patients (56%) had transient DSA. There was a trend towards lower 1-year-survival in DSA-positive compared with DSA-negative patients (83% vs 94%; P = 0.199). Remarkably, patients with persistent DSA had significantly reduced survival (1-year survival 60%) compared with both patients without DSA and those with transient DSA (P = 0.005). Persistent DSA represented as an independent prognostic factor for reduced overall survival in multivariate analysis (HR 8.3, 95% CI 1.8-37.0; P = 0.006). Persistence of DSA during the first year after transplantation seems to be more harmful for lung allograft function than transiently detected DSA at an early stage.